Effect of solid particles concentration to the size of graphene oxide liquid crystals pickering emulsion - Sahir, Nurul Nadiah; Hassan, Noor Azlina; Hassan, Norita; Johari, Norhasnidawani; Surip, Siti Norasmah (The Mattingley Publishing Co., Inc., 2020)
Graphene oxide (GO) sheets have been used as a colloidal surfactant in a Pickering emulsion system due to their amphiphilic property. They also show a liquid crystals behavior, which make them suitable to synthesize graphene oxide liquid crystals Pickering emulsion (GOLCsPE). Desired GOLCsPE sizes and stability can be obtained by controlling several parameters, especially the concentration of graphene oxide colloidal surfactant. This paper focused on the preparation of GOLCsPE with linseed oil as an internal phase. The GO concentration was varied in order to study their effect on GOLCsPE size and stability. The stability of the emulsion was observed through phase separation observation. Polarized optical microscope (POM) and particle size analyzer (PSA) were employed to characterize the size distribution of the GOLCsPE. POM analysis shows that increased in GO concentration led to the finer emulsion with the smallest droplet size around 8μm. However, the PSA analysis revealed otherwise. It was found that by increasing the amount of GO sheets, the GOLCsPE size will also increase, which could be caused by too many GO sheets laden around the oil droplets. The coefficient of variation (Cv) of the liquid crystals based on POM images showed a decreased, indicates the GO concentration improves the droplet size distribution. It also suggested that GO concentration plays a more important role in maintaining the stability of the GOLCsPE, rather than their sizes. By comparing both POM and PSA results, liquid crystals prepared with 3.7 mg/ml produced satisfied GOLCs diameter (around 8.5μm, Cv = 0.31) and stability. The shining halos around the droplets are proof that the GO acts as a colloidal surfactant and assembled themselves around the linseed oil droplets, forming a shell-like structure.